Franz Kafkaâ€™s Novel der Prozess (The Trial) As A Novel About Creative Endeavor, Choice and Faith - Sergeyevich Kunavin, Evgenii; ., . (International Journal of Engineering and Technology, 2018)
In this article, the author discusses the topic of adequate interpretation of F. Kafkaâ€™s novel The Trial, one of the most well-known works of literature of the early 20th century, this topic being very relevant for contemporary literature studies. The introduction states the purpose of the article, and points out that the theme of creative pursuits, which is touched upon in the writerâ€™s diaries and letters, is one of the main topics that help understand the environment in which the novel was created. The principal part of the paper reveals approaches used to analyze the novel. Additionally, the article discusses records from the writerâ€™s diary and letters; shows the direct link between the works and the biography of the Prague writer. The article presumes that the novel models a real-life situation. It argues S. Kierkegaard had an impact on F. Kafkaâ€™s writing, and uncovers a link between works of the Danish philosopher and the emergence of the novel. Moreover, the paper draws a conclusion on the role that F. Kafkaâ€™s lover, F. Bauer, played in creating The Trial, proposes a possible plot of the novel and summarizes observations on the work. In conclusion, the article speaks about the results of the â€œmodelingâ€ that F. Kafka obtained, and about the influence of that novel and S. Kierkegaardâ€™s ideas on the latter part of the Prague writerâ€™s career. Â Â Â